(untitled) (ENTHYMEMA, 2020)
The essay seeks to investigate some features of Italian poetry in the second half of the 1900s. It is specially focused on giving a historical perspective based on two points: to set free from conventions what is generally considered ‘lyrical poetry’ and ‘avant-gard poetry’; to consider poetry as a ‘social discourse’. Starting off from results of the first edition of the Seminario annuale sulla poesia italiana contemporanea (scientific board: Paolo Giovannetti, Stefano Giovannuzzi, Stefano Ghidinelli, Maria Borio, Lorenzo Cardilli), which took place at IULM University in April 2019, the essay is also an introduction to some of the speeches. It compares researches, anthologies and literary works, with particular attention to the period of the 70s, and aims to suggest an analysis which tries to shed new light on genealogies and relations between tendencies and works of literature.